Acceptability of Extended-Release Naltrexone by Heroin-Dependent Patients and Addiction Treatment Providers in the Netherlands. (5th December 2016) - Zaaijer, Eline R.; Goudriaan, Anna E.; Koeter, Maarten W. J.; Booij, Jan; van den Brink, Wim
ABSTRACT: Background : Extended-release naltrexone (XRNT) was developed to overcome poor treatment compliance with oral naltrexone in alcohol and opioid-dependent patients. XRNT injections are registered in the United States and Russia, but not in The Netherlands. However, XRNT can be obtained for individual patients, but it is expensive and not reimbursed by the health insurance. Objectives : This study evaluates the support for abstinence oriented treatment among heroin-dependent patients and the acceptability of XRNT injections by heroin-dependent patients and treatment providers in The Netherlands. Methods : A sample of 261 patients in methadone maintenance treatment or heroin assisted treatment and a sample of 188 addiction treatment providers completed specially designed questionnaires. Results : The current study shows that many patients in opioid maintenance treatment (58%) report a desire to become abstinent from opioids and that 83% of the patients with a desire for abstinence are interested in XRNT. The majority of treatment providers (81%) are willing to support the prescription of XRNT injections in opioid-dependent patients to prevent relapse after detoxification. Conclusions : The current practice of automatic and indefinite continuation of opioid substitution should therefore be reconsidered. However, XRNT injections are very expensive and currently not reimbursed by the health insurance agencies in The Netherlands and thus not really available to most patients.